PENGARUH PRODUCT QUALITY, SERVICE QUALITY, IMAGE TERHADAP LOYALTY MELALUI SATISFACTION PADA RESTORAN SUNDA DI JAKARTA - Dessy Pirbadi (Jurnal Manajemen dan Pemasaran Jasa, 2014)
Number of Sunda Restaurant’s consumer in the year of 2009 and 2012 are decreasing although the number of restaurant is increasing. This research test the impact of Product quality, Service quality, and Image through Satisfaction into consumer’s Loyalty by using Convenience Sampling with 200 respondents who have visited and eat in Sunda Restaurant in Jakarta at least twice in the last sixmonths. Tool used to analyze the data is Structural Equation Model (SEM) through AMOS software ver. 18.00. Result shows that Product quality, Service quality, Image, and Satisfaction have positive impact to Loyalty.Key words: Product quality, Service quality, Image, Satisfaction, Loyalty